A Causal Model for Psycho-social Aspects of Science Learning Environment on Academic Performance of Secondary School Students in Region X, Philippines (Proceedings of the International Conference on Future of Education, 2021)
The study geared to develop a causal model for the psychosocial attributes of the learningenvironment on Grade 10 students' science performance in secondary schools divisions of Region X,Northern Mindanao. This study utilized descriptive correlational and causal-comparative researchdesign. A random sample of 1,123 Grade 10 students was utilized in this study. Data were analyzedusing descriptive statistics, Correlation, Regression, and Path Analyses. The results revealed thatstudents' performance in Science was found out of low mastery level. In terms of psychosocialaspects, the students generally practiced their science activities in both laboratory and classroomenvironments, possessed moderate confidence in their emotion and self-efficacy in chemistry, havingaverage science process skills, and were mentored by science teachers with very satisfactoryteaching ability. Classroom environment and teacher ability were the psychosocial aspects thatsignificantly correlated with performance. The best-fitting causal model on students' performance isanchored on the classroom environment, supported by teachers' qualifications. A classroom learningenvironment that is highly conducive can stimulate students' interest to enhance their sciencelearning. It is highly recommended that administrators and policymakers revisit curricular activities,particularly on students' classroom learning environment in the teaching-learning process.
Keywords: academic performance; a causal model; and psychosocial aspects of the learning environment